Bakhtin and genre theory in biblical studies - Boer, Roland, 1961- (Society of Biblical Literature. Semeia studies ;, 2007)
This volume offers a meeting between genre theory in biblical studies and the work of Mikhail Bakhtin, who continues to be immensely influential in literary criticism. Here Bakhtin comes face to face with a central area of biblical studies: the question of genre. The essays range from general discussions of genre through the reading of specific biblical texts to an engagement with Toni Morrison and the Bible. --From publisher's description.